Preparation method of anti-shrinkage carbon fiber reinforced plastic

By combining the polymer blend with carbon fiber and undergoing electron beam irradiation and annealing, the problem of dimensional instability of engineering plastics during thermal expansion and contraction is solved, and the resistance to shrinkage, creep and oxidation is achieved. Effect, suitable for the production of high-precision products.

CN119463328AInactive Publication Date: 2025-02-18贾春宁
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373587.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing engineering plastics are prone to deform or break during thermal expansion and contraction, resulting in unstable product size and difficult to meet the high-precision and high-demand product production needs.

Method used

The polymer blend is combined with carbon fiber, and after electron beam irradiation and annealing, a shrink-resistant carbon fiber reinforced plastic is prepared.

Benefits of technology

It achieves the effects of resistance to shrinkage, creep and oxidation, enhances the mechanical properties and dimensional stability of plastics, and is suitable for the production of high-precision products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of anti-shrinkage carbon fiber reinforced plastic, and relates to the technical field of plastic. The ultra-high molecular weight polyethylene and the polypropylene are interpenetrated and entangled to form a microscopic interlaced network, so that the matrix achieves anti-shrinkage and anti-creep effects, in the blending process, two molecular chains tend to be directionally arranged under the action of a tensile flow field, and therefore the matrix is enhanced, and as the action time of the force field is prolonged, the anti-shrinkage and anti-creep effects are achieved. The nano silicon dioxide is used for filling, so that the base body realizes an anti-oxidation effect and an anti-shrinkage effect is enhanced; the preparation method comprises the following steps: firstly, preparing nano silicon dioxide, reinforcing creep resistance and shrinkage resistance of a matrix by using a carbon fiber net, then activating carbon fibers by irradiation, carrying out a bonding reaction with the nano silicon dioxide, coating a polymer, and carrying out irradiation and cross-linking on the polymer again, so that the matrix forms a denser structure, and finally, carrying out annealing treatment to reinforce cross-linking and improve the shrinkage resistance, creep resistance and oxidation resistance effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, in particular to a method for preparing shrinkage-resistant carbon fiber reinforced plastics. Background Art

[0002] With the vigorous development of my country's economy, the demand for high-performance plastics in the automotive, electronics and other fields is increasing. The high performance and practical application of engineering plastics can quickly, effectively and economically provide colorful new materials for national defense construction, various fields of the national economy and people's material and cultural life. However, the single category of components makes it have the common problem of plastic thermal expansion and contraction, which leads to unstable product size, easy deformation and even rupture; especially in the production of high-precision and high-requirement products, shrinkage directly affects the precision and quality of the product.

[0003] In order to be used as engineering plastics in a wider range of fields, people usually choose fibers as composite materials to enhance performance. Among them, carbon fiber is a material with extremely light weight but extremely high strength. Since its invention, more and more people have chosen it every year. Due to its excellent properties such as high strength, high modulus, light weight, excellent electrical conductivity and thermal conductivity, it has become one of the important reinforcing materials for the preparation of advanced composite materials. Compared with traditional engineering metals, it can form rigid parts with customized directional characteristics, thereby greatly reducing weight.

[0004] The development of the plastic products industry can not only prosper the fields of polymer materials and composite materials science and engineering, but also promote the development of the industry. Therefore, it is particularly necessary to invent a shrinkage-resistant carbon fiber reinforced plastic. Summary of the invention

[0005] The purpose of the present invention is to provide a shrinkage-resistant carbon fiber reinforced plastic and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a shrinkage-resistant carbon fiber reinforced plastic, wherein the shrinkage-resistant carbon fiber reinforced plastic is prepared by composite carbon fiber with a polymer blend and then subjected to irradiation treatment.

[0007] Furthermore, the polymer blend is prepared by blending ultra-high molecular weight polyethylene and polypropylene.

[0008] Furthermore, a method for preparing a shrinkage-resistant carbon fiber reinforced plastic comprises the following preparation steps: (1) The polymer blend with a bulk density of 0.483 g / cm 3 The polyethylene wax, pretreated silicon dioxide and lead stearate are mixed, blended and processed by a torque rheometer, and granulated to obtain a polymer; (2) placing a polymer in a mold with a thickness of 0.2 to 0.8 cm, covering it with a mesh woven from carbon fibers with a thickness of 0.5 to 2 mm, and performing a first electron beam irradiation treatment. Subsequently, a polymer with the same thickness as the bottom layer is compounded on the mesh, and a second irradiation is performed to obtain a carbon fiber reinforced polymer; (3) The carbon fiber reinforced polymer is annealed and left to stand at 0°C for 24 to 40 hours to obtain a shrinkage-resistant carbon fiber reinforced plastic.

[0009] Furthermore, the polymer blend in step (1) is composed of a polymer having a molecular weight of 9×10 7 Polyethylene, molecular weight is 9×10 4 and polypropylene in a mass ratio of 2:1, heated to 170-220°C, and stirred at 50-100rpm for 10-20min to obtain the product.

[0010] Furthermore, the preparation method of the pretreated silica in step (1) is as follows: anhydrous ethanol and deionized water are mixed in a mass ratio of 9:1, 0.75 times the mass of deionized water of KH550 are added, and the mixture is stirred at 120-200 rpm for 10 min, 0.5 times the mass of deionized water of nano-silicon dioxide are added, and the mixture is stirred for 1 h. The mixture is filtered, and the solid is taken and dried at 40-60° C. for 3-6 h.

[0011] Furthermore, the blending conditions in step (1) are as follows: temperature of 190° C., rotation speed of 50-70 rpm, and time of 5-20 min.

[0012] Furthermore, the polymer blend in step (1) has a bulk density of 0.483 g / cm 3 The mass ratio of polyethylene wax, pretreated silica and lead stearate is 50~70:20~30:0.1~1:0.05~0.1.

[0013] Furthermore, the weight of the carbon fiber mesh in step (2) is 150-250 g / m 2 , the strength is 3000~4500MPa.

[0014] Furthermore, the first electron beam irradiation conditions in step (2) are: irradiation dose of 100-400 kGy, time of 4-16 s, and the second irradiation conditions are: irradiation dose of 50-200 kGy, temperature of 60-120° C., time of 2-5 min.

[0015] Furthermore, the annealing conditions in step (3) are: nitrogen atmosphere, temperature of 110° C., and time of 2 h.

[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: The plastic of the invention is prepared by composite carbon fiber with a polymer blend and then subjected to irradiation treatment to achieve the effects of anti-shrinkage, anti-creep and anti-oxidation.

[0017] Firstly, the two macromolecular polymers, ultra-high molecular weight polyethylene and polypropylene, are interpenetrated and entangled with each other to form a microscopic interwoven network, which restricts the free movement of long molecular chains and reduces the distance between molecular chains, thereby enhancing the interaction force between matrices and achieving the effects of anti-shrinkage and anti-creep. During the blending process, the stretching flow field is used to make the matrix repeatedly shrink and expand, so that the two flexible molecular chains tend to be arranged in a directional manner along the flow direction during the processing, avoiding the three-dimensional topological structure formed by the molecular chains due to the long blending time, and orientation-induced crystallization occurs, thereby strengthening the matrix, improving the anti-shrinkage and anti-creep effects, and giving the matrix and the effective ingredients good dispersibility, so that the phase interface is enlarged, and a synergistic effect can be exerted. As the force field action time increases, the molecular chains expand and diffuse, and nano-silicon dioxide is gradually infiltrated into them to avoid the formation of a hole structure in the matrix. Even during thermal expansion and cooling, no morphological changes occur, thereby achieving antioxidant and enhanced anti-shrinkage effects.

[0018] Secondly, the carbon fiber reinforced matrix is ​​used to absorb the expansion energy during the destruction process. Then, it is woven into a mesh structure and covered on the polymer, so that the matrix can effectively reduce the occurrence of layer damage under the action of in-plane compression, bending, fatigue and lateral impact loads. This reinforcement effect enhances the creep resistance of the matrix, and the composite material achieves a strong shrinkage resistance effect under the constraint of the carbon fiber skeleton. Then, the carbon fiber is activated by radiation, and a bonding reaction occurs with nano-silicon dioxide. The carbon fiber is then covered with a polymer and the composite is cross-linked by radiation again. As the radiation dose increases, the cross-linking effect is enhanced, and the gel content in the polymer also increases, so that most of the free radicals undergo cross-linking reactions in the amorphous region, resulting in radial shrinkage reactions of the molecular chains, forming a denser structure for the matrix, and increasing the bonding between the carbon fiber and the polymer, thereby enhancing the shrinkage and creep resistance of the plastic. Finally, annealing treatment is used to accelerate the cross-linking reaction of the free radicals to prevent subsequent oxidation of the matrix surface and improve the antioxidant effect. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the shrinkage-resistant carbon fiber reinforced plastics prepared in the following examples are as follows: Shrinkage resistance: Take the embodiment and the comparative example of the same size and test their transverse and longitudinal shrinkage rates according to GB / T17037.4.

[0021] Creep resistance: The same size of the embodiment and the comparative example were taken to test the tensile creep modulus according to GB / T11546.1, the test temperature was 180°C, and the test time was 2 min.

[0022] Antioxidation: Take the embodiment and comparative example of the same size, select a ventilated thermal aging oven, place them at 100°C for 60 days, take them out and cool them to room temperature, and observe whether the sample surface is deformed or cracked.

[0023] Example 1 (1) The molecular weight is 9×10 7 Polyethylene, molecular weight is 9×10 4 The polypropylene was mixed in a mass ratio of 2:1, heated to 170°C, and stirred at 50rpm for 10min to obtain a polymer blend; anhydrous ethanol and deionized water were mixed in a mass ratio of 9:1, KH550 with a mass of 0.75 times the mass of deionized water was added, stirred at 120rpm for 10min, nano-silicon dioxide with a mass of 0.5 times the mass of deionized water was added, and stirring was continued for 1h, filtered, and the solid was taken and dried at 40°C for 3h to obtain pretreated silicon dioxide; the polymer blend and the bulk density of 0.483g / cm 3 The polyethylene wax, pretreated silica and lead stearate were mixed, placed in a torque rheometer, treated at 190°C and a rotation speed of 50 rpm for 5 minutes, and granulated to obtain a polymer; the polymer blend had a bulk density of 0.483 g / cm 3 The mass ratio of polyethylene wax, pretreated silica, and lead stearate is 50:20:0.1:0.05; (2) Place the polymer in a mold with a thickness of 0.2 cm and weave the carbon fiber into a 150 g / m 2 A mesh material with a strength of 3000MPa is covered on it with a thickness of 0.5mm, and the first electron beam irradiation treatment is carried out, and the irradiation dose is 100kGy and the time is 4s. Then, a polymer with the same thickness as the bottom layer is compounded on the mesh material, and the second irradiation is carried out at 60°C, and the irradiation dose is 50kGy and the time is 2min, thereby obtaining a carbon fiber reinforced polymer; (3) The carbon fiber reinforced polymer is annealed in a nitrogen atmosphere at 110°C for 2 h and then placed at 0°C for 24 h to obtain a shrinkage-resistant carbon fiber reinforced plastic.

[0024] Example 2 (1) The molecular weight is 9×10 7 Polyethylene, molecular weight is 9×10 4 The mixture was mixed with polypropylene in a mass ratio of 2:1, heated to 190°C, and stirred at 75rpm for 15min to obtain a polymer blend; anhydrous ethanol and deionized water were mixed in a mass ratio of 9:1, KH550 with a mass of 0.75 times the mass of deionized water was added, stirred at 160rpm for 10min, nano-silicon dioxide with a mass of 0.5 times the mass of deionized water was added, and the mixture was stirred for 1h, filtered, and the solid was taken and dried at 50°C for 4h to obtain pretreated silicon dioxide; the polymer blend and the bulk density of 0.483g / cm 3 The polyethylene wax, pretreated silica and lead stearate were mixed and placed in a torque rheometer. The mixture was treated at 190°C and a rotation speed of 60 rpm for 10 min and granulated to obtain a polymer. The polymer blend had a bulk density of 0.483 g / cm 3 The mass ratio of polyethylene wax, pretreated silica, and lead stearate is 60:25:0.6:0.08; (2) Place the polymer in a mold with a thickness of 0.5 cm and weave the carbon fiber into a 200 g / m 2 A mesh material with a strength of 4000MPa is covered on it with a thickness of 1.2mm, and the first electron beam irradiation treatment is carried out, and the irradiation dose is 200kGy and the time is 10s. Then, a polymer with the same thickness as the bottom layer is compounded on the mesh material, and the second irradiation is carried out at 90°C, and the irradiation dose is 100kGy and the time is 3min, thereby obtaining a carbon fiber reinforced polymer; (3) The carbon fiber reinforced polymer is annealed in a nitrogen atmosphere at 110°C for 2 h and then allowed to stand at 0°C for 32 h to obtain a shrinkage-resistant carbon fiber reinforced plastic.

[0025] Example 3 (1) The molecular weight is 9×10 7 Polyethylene, molecular weight is 9×10 4 The mixture was mixed with polypropylene in a mass ratio of 2:1, heated to 220°C, and stirred at 100rpm for 20min to obtain a polymer blend; anhydrous ethanol and deionized water were mixed in a mass ratio of 9:1, KH550 with a mass of 0.75 times the mass of deionized water was added, stirred at 200rpm for 10min, nano-silicon dioxide with a mass of 0.5 times the mass of deionized water was added, and the mixture was stirred for 1h, filtered, and the solid was taken and dried at 60°C for 6h to obtain pretreated silicon dioxide; the polymer blend and the bulk density of 0.483g / cm 3 The polyethylene wax, pretreated silica and lead stearate were mixed, placed in a torque rheometer, treated at 190°C and a rotation speed of 70 rpm for 20 minutes, and granulated to obtain a polymer; the polymer blend had a bulk density of 0.483 g / cm 3The mass ratio of polyethylene wax, pretreated silica, and lead stearate is 70:30:1:0.1; (2) Place the polymer in a mold with a thickness of 0.8 cm and weave the carbon fiber into a 250 g / m 2 A mesh material with a strength of 4500MPa is covered on it with a thickness of 2mm, and the first electron beam irradiation treatment is carried out, with an irradiation dose of 400kGy and a time of 16s. Then, a polymer with the same thickness as the bottom layer is compounded on the mesh material, and a second irradiation is carried out at 120°C with an irradiation dose of 200kGy and a time of 5min to obtain a carbon fiber reinforced polymer; (3) The carbon fiber reinforced polymer is annealed in a nitrogen atmosphere at 110°C for 2 h and then allowed to stand at 0°C for 40 h to obtain a shrinkage-resistant carbon fiber reinforced plastic.

[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: anhydrous ethanol and deionized water are mixed in a mass ratio of 9:1, KH550 with a mass of 0.75 times that of deionized water is added, and the mixture is stirred at 160 rpm for 10 min, nano-silica with a mass of 0.5 times that of deionized water is added, and the mixture is stirred for 1 h. The mixture is filtered, and the solid is taken and dried at 50°C for 4 h to obtain pretreated silica; a 9×10 7 Polyethylene, bulk density is 0.483g / cm 3 The polyethylene wax, pretreated silica and lead stearate were mixed and placed in a torque rheometer. The mixture was treated at 190°C and a rotation speed of 60 rpm for 10 min and granulated to obtain a polymer. The molecular weight was 9×10 7 Polyethylene, bulk density is 0.483g / cm 3 The mass ratio of polyethylene wax, pretreated silica, and lead stearate is 60:25:0.6:0.08; the remaining steps are the same as in Example 2.

[0027] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: 7 Polyethylene, molecular weight is 9×10 4 The polymer blend was prepared by mixing the polymer and the polypropylene in a mass ratio of 2:1, heating to 190°C, stirring at 75 rpm for 15 min, and obtaining a polymer blend; the polymer blend and the bulk density of 0.483 g / cm 3 The polyethylene wax and lead stearate are mixed, placed in a torque rheometer, treated at 190°C and a rotation speed of 60 rpm for 10 minutes, and granulated to obtain a polymer; the polymer blend has a bulk density of 0.483 g / cm 3The mass ratio of polyethylene wax and lead stearate is 60:25:0.08; the remaining steps are the same as those in Example 2.

[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (1) is different. Step (1) is changed to: 7 Polyethylene, molecular weight is 9×10 4 The mixture was mixed with polypropylene in a mass ratio of 2:1, heated to 190°C, and stirred at 75rpm for 15min to obtain a polymer blend; anhydrous ethanol and deionized water were mixed in a mass ratio of 9:1, KH550 with a mass of 0.75 times the mass of deionized water was added, stirred at 160rpm for 10min, nano-silicon dioxide with a mass of 0.5 times the mass of deionized water was added, and the mixture was stirred for 1h, filtered, and the solid was taken and dried at 50°C for 4h to obtain pretreated silicon dioxide; the polymer blend and the bulk density of 0.483g / cm 3 The polyethylene wax, pretreated silica and lead stearate were mixed, stirred at 190°C and 60rpm for 10min, and granulated to obtain a polymer; the polymer blend had a bulk density of 0.483g / cm 3 The mass ratio of polyethylene wax, pretreated silica, and lead stearate is 60:25:0.6:0.08; the remaining steps are the same as in Example 2.

[0029] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: the polymer and carbon fiber are mixed in a mass ratio of 10:0.5, the temperature is raised to 90° C., and electron beam irradiation is performed with an irradiation dose of 100 kGy and a time of 3 min to obtain a carbon fiber reinforced polymer; the remaining steps are the same as in Example 2.

[0030] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that step (2) is different. Step (2) is changed to: the polymer is woven into a carbon fiber with a gram weight of 200 g / m 2 , and a mesh material with a strength of 4000 MPa is coated, and then irradiated with an electron beam, with an irradiation dose of 100 kGy, a temperature of 90° C., and a time of 3 min to obtain a carbon fiber reinforced polymer; the remaining steps are the same as in Example 2.

[0031] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that step (2) is different. Step (2) is changed to: placing a polymer in a mold with a thickness of 0.5 cm, weaving the carbon fiber into a 200 g / m 2A mesh material with a strength of 4000 MPa and a thickness of 1.2 mm is covered on it, and electron beam irradiation treatment is performed with an irradiation dose of 200 kGy for 10 s. Subsequently, a polymer with the same thickness as the bottom layer is compounded on the mesh material to obtain a carbon fiber reinforced polymer. The remaining steps are the same as in Example 2.

[0032] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that step (2) is different. Step (2) is changed to: the polymer pair is woven into a carbon fiber with a gram weight of 200 g / m 2 , and wrapping with a mesh material with a strength of 4000 MPa to obtain a carbon fiber reinforced polymer; the remaining steps are the same as in Example 2.

[0033] Comparative Example 8 The difference between Comparative Example 8 and Example 2 is that there is no step (3), and step (2) is changed to: placing a polymer in a mold with a thickness of 0.5 cm, weaving the carbon fiber into a 200 g / m 2 A mesh material with a strength of 4000MPa and a thickness of 1.2mm is covered on it, and the first electron beam irradiation treatment is carried out, and the irradiation dose is 200kGy and the time is 10s. Then, a polymer with the same thickness as the bottom layer is compounded on the mesh material, and the second irradiation is carried out at 90°C, and the irradiation dose is 100kGy and the time is 3min. It is placed at 0°C and allowed to stand for 32h to obtain a shrinkage-resistant carbon fiber reinforced plastic. The remaining steps are the same as those in Example 2.

[0034] Effect example Table 1 below shows the performance analysis results of the shrinkage-resistant carbon fiber reinforced plastics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0035] Table 1

[0036] From the comparison of the experimental results of the embodiment and the comparative example in Table 1, it can be found that, firstly, the two macromolecular polymers of ultra-high molecular weight polyethylene and polypropylene are mutually intertwined and entangled to form a microscopic interwoven network, thereby enhancing the interaction force between the matrices and achieving the effects of anti-shrinkage and anti-creep. In the blending process, the effect of the stretching flow field is utilized to make the two flexible molecular chains tend to be oriented along the flow direction during the processing, thereby strengthening the matrix, improving the anti-shrinkage and anti-creep effects, and giving the matrix and the effective ingredients good dispersibility, so that the phase interface is enlarged. As the force field action time is prolonged, the molecular chains expand and diffuse, and nano-silicon dioxide is gradually infiltrated therein to avoid the formation of a hole structure in the matrix. Even in the process of thermal expansion and cooling, no morphological change occurs, thereby achieving anti-oxidation and enhancing the anti-shrinkage effect; carbon fiber is used to strengthen the matrix. The body absorbs the expansion energy during the destruction process and weaves it into a mesh structure, which is covered on the polymer, so that the matrix can strengthen the creep resistance of the matrix under the action of in-plane compression, bending, fatigue and lateral impact loads, and the composite material achieves a strong anti-shrinkage effect under the constraint of the carbon fiber skeleton. Then, the carbon fiber is activated by radiation, and a bonding reaction occurs with nano-silicon dioxide. The carbon fiber is then covered with a polymer, and the composite is cross-linked by radiation again. As the radiation dose increases, the cross-linking effect is enhanced, so that most of the free radicals undergo cross-linking reactions in the amorphous region, so that the matrix forms a denser structure, and the bonding between the carbon fiber and the polymer is increased, thereby enhancing the shrinkage and creep resistance of the plastic. Finally, annealing is performed to accelerate the cross-linking reaction of the free radicals to prevent subsequent oxidation of the matrix surface and improve the antioxidant effect.

[0037] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a shrinkage-resistant carbon fiber reinforced plastic, characterized in that: The method comprises the following preparation steps: (1) The molecular weight is 9×10 7 Polyethylene, molecular weight is 9×10 4 The mixture was mixed with polypropylene in a mass ratio of 2:1, heated to 190°C, and stirred at 75rpm for 15min to obtain a polymer blend; anhydrous ethanol and deionized water were mixed in a mass ratio of 9:1, KH550 with a mass of 0.75 times the mass of deionized water was added, stirred at 160rpm for 10min, nano-silicon dioxide with a mass of 0.5 times the mass of deionized water was added, and the mixture was stirred for 1h, filtered, and the solid was taken and dried at 50°C for 4h to obtain pretreated silicon dioxide; the polymer blend and the bulk density of 0.483g / cm 3 The polyethylene wax, pretreated silica and lead stearate were mixed and placed in a torque rheometer. The mixture was treated at 190°C and a rotation speed of 60 rpm for 10 min and granulated to obtain a polymer. The polymer blend had a bulk density of 0.483 g / cm 3 The mass ratio of polyethylene wax, pretreated silica, and lead stearate is 60:25:0.6:0.08; (2) Place the polymer in a mold with a thickness of 0.5 cm and weave the carbon fiber into a 200 g / m 2 A mesh material with a strength of 4000MPa is covered on it with a thickness of 1.2mm, and the first electron beam irradiation treatment is carried out, and the irradiation dose is 200kGy and the time is 10s. Then, a polymer with the same thickness as the bottom layer is compounded on the mesh material, and the second irradiation is carried out at 90°C, and the irradiation dose is 100kGy and the time is 3min, thereby obtaining a carbon fiber reinforced polymer; (3) The carbon fiber reinforced polymer is annealed in a nitrogen atmosphere at 110°C for 2 h and then allowed to stand at 0°C for 32 h to obtain a shrinkage-resistant carbon fiber reinforced plastic.